Does corruption hamper bank lending? Macro and micro evidence - Laurent Weill (Bank of Finland, Institute for Economies in Transition (BOFIT), 2009)
The aim of this paper is to analyze the effect of corruption in bank lending. Corruption is expected to hamper bank lending, as it is closely related to legal enforcement, which has been shown to promote banks' willingness to lend. Nevertheless the similarities between the consequences for bank lending of law enforcement and corruption are misleading, as they consider only judiciary corruption. Corruption can also occur in lending and may then be beneficial for bank lending via bribes given by borrowers to enhance their chances of receiving loans. This assumption may be validated particularly in the presence of pronounced risk aversion by banks, resulting in greater reluctance on the part of banks to grant loans. We perform country-level and bank-level estimations to investigate these assumptions. Corruption reduces bank lending in both sets of estimations. However, bank-level estimations show that the detrimental effect of corruption is reduced when bank risk aversion increases, even leading at times to situations wherein corruption fosters bank lending. Additional controls show that corruption does not increase bank credit by favoring only bad loans. Therefore, our findings show that while the overall effect of corruption is to hamper bank lending, it can alleviate firm's financing obstacles.
URN:NBN:fi:bof-201408071985
Keywords: G20; O5; 330; Corruption; bank; financial development